1999
DOI: 10.4319/lo.1999.44.3.0662
|View full text |Cite
|
Sign up to set email alerts
|

Acetogenesis from CO2 in an anoxic marine sediment

Abstract: A combination of radiotracer and pore-water concentration measurements provide evidence for the occurrence of acetogenesis from CO 2 in anoxic marine sediments that are ordinarily dominated by sulfate reduction and methanogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 30 publications
6
30
1
1
Order By: Relevance
“…This phenomenon is consistent with the observed (23, 24) accumulation of labile VFAs in anoxic marine sediments for which no mechanism had been identified (25). Although shifts in the microbial community composition could explain varying patterns of substrate abundance (26), VFA accumulation at low temperatures in the absence of apparent microbial population transitions or substrate limitations has been documented (6,(23)(24)(25)27), and differential temperature responses of functional microbial groups can explain such results. The temperature-limited capacity of the hydrolytic͞fermentative production of labile LMW-DOC during the summer months may generate a ''bottleneck'' in organic matter mineralization, leading to carbon limitation of the terminal metabolic microbial community at certain times of year.…”
Section: Discussionsupporting
confidence: 85%
“…This phenomenon is consistent with the observed (23, 24) accumulation of labile VFAs in anoxic marine sediments for which no mechanism had been identified (25). Although shifts in the microbial community composition could explain varying patterns of substrate abundance (26), VFA accumulation at low temperatures in the absence of apparent microbial population transitions or substrate limitations has been documented (6,(23)(24)(25)27), and differential temperature responses of functional microbial groups can explain such results. The temperature-limited capacity of the hydrolytic͞fermentative production of labile LMW-DOC during the summer months may generate a ''bottleneck'' in organic matter mineralization, leading to carbon limitation of the terminal metabolic microbial community at certain times of year.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, this zone is often accompanied by peak hydrogen sulfide and bicarbonate concentrations. Laboratory experiments demonstrated that during the transition from sulfate reduction to methanogenesis, there is a decoupling of H 2 production and consumption and hence a temporary accumulation of H 2 (Hoehler et al, 1999). Isotopic evidence for acetogenesis via CO 2 reduction in an extended sediment interval just below the SMTZ at the Cascadia Margin is also consistent with elevated H 2 concentration in situ (Heuer et al, 2009).…”
Section: Implications For Anoxic Environmentssupporting
confidence: 51%
“…Although the amount of sulfate (0.16 mM) may be above the threshold for sulfate reduction, at least some of this may be the product of recent sulfide oxidation. Inhibition of SRB, which usually outcompete homoacetogens for H 2 , could explain the detection of hydrogen and the abundance of acetogens in the lake (Hoehler et al, 1999).…”
Section: Discussionmentioning
confidence: 99%